Census of Jail Facilities, 2006 ([Verlag nicht ermittelbar], 2010)
To reduce respondent burden and improve data quality and timeliness, the Bureau of Justice Statistics (BJS) split the jail census into two parts: The Census of Jail Inmates was conducted with a reference date of June 30, 2005. The following spring it was followed by this enumeration, the Census of Jail Facilities, which collected data as of March 31, 2006. Previous jail enumerations were conducted in 1970 (ICPSR 7641), 1972 (ICPSR 7638), 1978 (ICPSR 7737), 1983 (ICPSR 8203), 1988 (ICPSR 9256), 1993 (ICPSR 6648), and 1999 (ICPSR 3318). The United States Census Bureau collected the data for the Bureau of Justice Statistics. The 2006 Census of Jail Facilities gathered data from all jail detention facilities holding inmates beyond arraignment, a period normally exceeding 72 hours. Jail facilities were operated by cities and counties, by private entities under contract to correctional authorities, and by the Federal Bureau of Prisons (BOP). Excluded from the census were physically separate temporary holding facilities such as drunk tanks and police lockups that do not hold persons after being formally charged in court. Also excluded were state-operated facilities in Connecticut, Delaware, Hawaii, Rhode Island, Vermont, and Alaska, which have combined jail-prison systems. Fifteen independently operated jails in Alaska were included in the Census. The census collected jurisdictional level information on the number of confined inmates; average daily population; number of separate jail facilities; renovation and building plans; court orders and consent decrees; staff by occupational category and race/ethnicity; jail programs; and costs of operation. The census also collected individual jail facility information on the purpose for which the jail held offenders; gender of the inmates authorized to house; functions, such as general adult population confinement, work release, and medical treatment; whether a separate temporary holding area or lockup was operated; rated capacity; number of confined inmates by gender and adult or juvenile status; year of original construction; and whether the facility ever had a major renovation.